On the periodic orbits of the third-order differential equation x ′′′ − µx ′′ + x ′ − µx = εF (x, x ′ , x ′′) - Llibre, Jaume; Roberto, Luci Any Francisco [UNESP] (Elsevier, 2013)
In this paper we study the periodic orbits of the third-order differential equation x ′′′−µx ′′+ x ′ − µx = εF (x, x ′ , x ′′), where ε is a small parameter and the function F is of class C 2 .
Keywords: periodic orbit; averaging method